PARTICIPATION OF RAILWAY DEPARTMENT AND RAILWAYS IN ASSISTING THE ARMY AND POPULATION DURING THE FIRST WORLD WAR - A. I. Narezhny; M. V. Pyatikova (Гуманитарные и юридические исследования)
The article highlights such important aspect of the First World War as charity. The authors analyzed the process of creation and functioning of departmental and «hybrid» charity model combining bureaucratic, private and proprietary and public basis. Revealed activities of the Office of Communications in the process of providing assistance to the Russian military personnel. The authors analyzed a variety of activities of the Main Committee to assist people affected by military action: the organization of sanitary trains, train-baths, hospitals, infirmaries, material assistance. This article underlines the importance of women's committees, working on a voluntary basis.